1ISG-009 Budget impact analysis of a natalizumab extended interval dosing regimen. (24th March 2020) - Pierobon, E; Mastrogiacomo, A; Capano, F; Ielo, D
Abstract : Background and importance: Natalizumab is a monoclonal antibody that blocks the immune reaction evoked during multiple sclerosis (MS) attacks but it could also weaken immunosurveillance, leading to an increased risk of developing progressive multifocal leucoencephalopathy (PML). Many studies have demonstrated that extended interval dosing (EID) of natalizaumab 300 mg every 6 weeks has the same efficacy as standard interval dosing (SID) every 4 weeks, but with a lower risk of PML. Aim and objectives: To compare the costs of SID and EID administration of natalizumab and to estimate the savings associated with EID. Material and methods: The analysis was carried out adopting a 3 year time horizon, the hospital perspective (corresponding to the National Health Service) and considering only the direct costs of the drug's purchase price. The population was patients diagnosed with MS and already being treated with the SID regimen at our hospital. The model used was based on real clinical data: patients were selected from September 2016 to September 2019. The annual cost considered 12 infusions for SID and 8 for EID of natalizumab, according to the actual regional public tender, which is mandatory (no possibility of further paybacks or discounts, or planned changes to the purchase agreement in the next 3 years). Three different scenarios were considered: 75%, 85% and 95% of patients on the EID regimen and the remaining on the SID regimen, based on the clinical judgment that almost all patients could benefit from an EID regimen, but the possibility should also be foreseen that a patient could not wait more than 4 weeks between infusions. Results: In the first scenario, there were 512 patients receiving EID and 171 SID, corresponding to a total cost of €10 490 101, or €13 986 802 if all patients were receiving SID. Treating 75% of patients with EID could reach a saving of €3 496 700. The second scenario (581 vs 102) generated a cost of €10 023 875 and a saving of €3 962 927, and the third scenario (649 vs 34) a total cost of €9 557 648 with a saving of €4 429 154. Conclusion and relevance: The analysis underlines the large savings in direct costs if most patients are infused every 6 weeks. This also corresponds to lower administration related costs (indirect costs) that could be calculated in a future analysis. References and/or acknowledgements: No conflict of interest.